Prevalence of rifampicin resistance by automated Genexpert rifampicin assay in patients with pulmonary tuberculosis in Yenagoa, Nigeria - Ikuabe, Peter Ogie (Pan Afr Med J, 2018)
INTRODUCTION: The diagnosis of tuberculosis and its treatment is challenging in resource – limited settings. The growth and speed of multi drug – resistant tuberculosis (MDR-TB) in high burden countries like Nigeria is a growing concern. This study is aimed at determining the prevalence of rifampicin resistance in sputum specimens of patients with pulmonary tuberculosis in Yenagoa, Nigeria. METHODS: A descriptive survey of all consecutive sputum specimens of adults greater than 15 years of age that presented to the Tuberculosis Referral Hospital Laboratory were subjected to the automated Genexpert test between January and December 2016. RESULTS: All 446 specimens were tested using the Genexpert automated system. 102 (22.9%) of the sputum specimens were positive for Mycobacterium tuberculosis, with 15 (14.7%) showing rifampicin resistance. CONCLUSION: There was significantly high prevalence of MDR-TB much higher than the World Health Organisation (WHO) prediction of 3.2 -5.4% for Nigeria. Pan African Medical Journal – ISSN: 1937- 8688 (www.panafrican-med-journal.com) Published in partnership with the African Field Epidemiology Network (AFENET). (www.afenet.net) Pan African Medical Journal – ISSN: 1937- 8688 (www.panafrican-med-journal.com) Published in partnership with the African Field Epidemiology Network (AFENET). (www.afenet.net)